Psychosocial factors of participation in family planning to understand context: A case of Chinese communities in an Islamic-based municipality - Sa'i, Sa'i; Syahabuddin, Khairiah; Salasiah, Cut Intan; Manan, Abdul; Ladele, Omolola Aina; Maulida, Maulida (UIN Ar-Raniry Banda Aceh, 2026)
This study examines the historical background of the Chinese community in Banda Aceh, the current implementation of the Family Planning (FP) program, and how the community perceives and understands the program as one of the government’s public welfare initiatives. The research employed a qualitative approach using observation, semi-structured interviews, and documentation as the primary data collection techniques. Ten married participants were selected through purposive sampling because they were considered capable of providing relevant and in-depth information in terms of specific characteristics, experiences, or knowledge relevant to family planning practices within the Chinese community. The findings reveal that the Chinese community in Banda Aceh perceives family planning not merely as a method to limit births, but as a strategy for navigating familial relationships and achieving enduring well-being. Many families view FP as an investment to enhance their quality of life, especially by ensuring children's education and household economic stability. This perspective reflects cultural values that emphasize careful future planning and the continuity of family businesses. Consequently, some participants prefer long-term contraceptive methods such as implants because they are considered practical and compatible with demanding work schedules in trade and business activities. The study also reveals that reproductive decisions are influenced by religious teachings, ancestral traditions, and social environments. Buddhist and Confucian beliefs generally support responsible parenting and do not prohibit birth regulation. However, traditional expectations regarding lineage continuity, especially the preference for sons, still shape reproductive decisions among many families.